Modelling the impact of local policies to optimise the development of electric vehicles. - Mousseau, Benjamin; Fulda, Anne-Sophie; Emberger, Guenter (My University, 2013)
In this project, scenarios for urban transport policies are simulated using the Land Use Transport Interaction (LUTI) "MARS" (Metropolitan Activity Relocation Simulator) model. This model had been used in the previous project "MARS-VE" to evaluate the impact of the policies and the effects of electric vehicles (EVs) on modal split, traffic volume, energy consumed and CO2 emissions. Three scenarios make it possible to analyse different penetration rates of EVs and the impact of local policies on promoting the use of EVs. The application in Mulhouse shows some first results. The Integration of EVs should be carried out within a framework of local policy in order to limit total traffic volume. The implementation of these local policies should be different in City centres and than in the outskirts of cities.
Keywords: Verkehr; Flächennutzung; Stadtregion; Elektromobilität; Kohlendioxid; CO2-Emission; Emissionsminderung; Kommunaler Klimaschutz; Verkehrspolitik